2010
DOI: 10.1159/000285283
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Nonprescription Use: A Cross-Sectional Hospital-Based Study in Basrah

Abstract: Objective: To study the prevalence and attitude of using nonprescription corticosteroids (oral or parenteral formulation of glucocorticosteroids) in Basrah, Iraq. Methods: A face-to-face model structured interview was used to collect information from 682 patients between January 2006 and December 2008. The following information was obtained: age, gender, marital status, smoking, drinking of alcohol, occupation, educational level, social class and place of residence. Results: Of the 682 (2.6%) subjects using no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 41 publications
8
22
1
Order By: Relevance
“…Self‐reported use of all drugs (prescription and illicit) was generally low and almost non‐existent among females. Consistent with a previous Iraqi study , the most commonly reported drug by men was steroids. Due to the cultural sensitivity of the survey topic, we suspect under‐reporting of substance use in this survey.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Self‐reported use of all drugs (prescription and illicit) was generally low and almost non‐existent among females. Consistent with a previous Iraqi study , the most commonly reported drug by men was steroids. Due to the cultural sensitivity of the survey topic, we suspect under‐reporting of substance use in this survey.…”
Section: Discussionsupporting
confidence: 87%
“…Our estimate of life‐time alcohol use in Iraq is approximately twice what is reported in the Iraqi Mental Health Survey in 2007 . There is poor coverage of alcohol use in Arab‐world studies, and most reports only involve life‐time use . Despite the low prevalence of alcohol use found in our study, the average number of drinks consumed among those who reported drinking was quite high (seven drinks per day).…”
Section: Discussioncontrasting
confidence: 68%
“…[15][16] A majority of HPAD seen in our Center is due to use of exogenous corticosteroids for various reasons, but most of them are due to nonprescription use. [13] This is established fact, all over the world. [16] Adrenal insufficiency after discontinuation of glucocorticoid occurs frequently; there is no administration form, dosing, treatment duration, or underlying disease for which adrenal insufficiency it can be excluded with certainty.…”
Section: Discussionmentioning
confidence: 95%
“…Similar finding seen from the same Center before, where women constituted 69% of those self-prescribed corticosteroids. [13] In a study by Hahner et al, women to men ratio for secondary AI were 113:77 with median age of 59 years. [18] The female predominance for HPAD is due to more use of corticosteroids in our patients that difficult to explain.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation